Inhibition effect of amino acids on carbon dioxide hydrate - Bavoh, C.B. (Elsevier Ltd, 2017)
The formation of gas hydrates hinders oil & gas transportation in pipelines, however, adequate knowledge and understanding of the gas hydrate phase behaviour is a key to its prevention. Thus, this study reports the inhibition effect of glycine, alanine, proline, serine and arginine on the carbon dioxide hydrate phase equilibrium condition using the isochoric T-cycle method in the pressure range of 2.53–4.0 MPa. The studied amino acids concentrations ranged from 5 to 20 wt. The presence of all the studied amino acids significantly shifted the carbon dioxide hydrate phase boundary to higher pressures and/or lower temperatures area, hence indicating inhibition effect. Glycine is found to show the highest inhibition strength with an average depression temperature of 1.83 K at 10 wt. In agreement with COSMO-RS sigma profile analysis, the amino acids inhibitions strengths are found to be influenced by their ability to reduce water activity in hydrate formation via hydrogen bonding with water molecules. The calculated carbon dioxide hydrate dissociation enthalpies in the presence of amino acids, suggested that, amino acids do not take part in carbon dioxide hydrate cage occupation and structure during hydrate formation. Furthermore, the measured carbon dioxide hydrate phase conditions in the presence of amino acids are predicted and are found to be in good agreement with the experimental data. © 2017 Elsevier Ltd